2017
DOI: 10.1080/19312458.2017.1317337
|View full text |Cite
|
Sign up to set email alerts
|

How Much Time Do You Spend Online? Understanding and Improving the Accuracy of Self-Reported Measures of Internet Use

Abstract: How much time do you spend online? Understanding and improving the accuracy of self-reported measures of internet use Araujo, T.B.; Wonneberger, A.; Neijens, P.C.; de Vreese, C.H. : 10.1080/19312458.2017.1317337 Link to publication Published in: Communication Methods and Measures DOI Citation for published version (APA):Araujo, T., Wonneberger, A., Neijens, P., & de Vreese, C. (2017). How much time do you spend online? Understanding and improving the accuracy of self-reported measures of internet use. Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 38 publications
6
149
0
Order By: Relevance
“…Another problem is that people are unlikely to recollect exactly when they did what 4,5 . Recent studies that compared survey responses with computer logs of behaviour indicate that people both under-and over-report media exposure -often by as much as several hours per day [6][7][8] . In today's complex media environment, survey questions about the past month or even the past day might be almost useless.…”
Section: Screen Timementioning
confidence: 99%
“…Another problem is that people are unlikely to recollect exactly when they did what 4,5 . Recent studies that compared survey responses with computer logs of behaviour indicate that people both under-and over-report media exposure -often by as much as several hours per day [6][7][8] . In today's complex media environment, survey questions about the past month or even the past day might be almost useless.…”
Section: Screen Timementioning
confidence: 99%
“…All behaviors were self-reported which can result in biased estimates. 50,51 Social media use was not directly assessed. Given the ubiquity of social media use among adolescents, screen time is likely underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the challenges of traffic measurement of user behaviour, mixed methods and triangulation have been recommended, but they are not yet common (see Findhal et al, 2014;Giglietto et al, 2012;Lagerstedt et al, 2012). Some studies have combined observed online data with other methods (e.g., Araujo et al, 2017;Scharkow, 2016), but few have used triangulation. Findahl and colleagues (2014) and Lagerstedt and colleagues (2012) studied internet audience behaviour through triangulation of traffic data measurements and surveys and diaries, adopting a meta-perspective.…”
Section: Example 2: Triangulation Of Big(ger) Data and Virtual Methodmentioning
confidence: 99%
“…The traffic measurements showed that the virtual methods did not give an incorrect but an incomplete picture of users' behaviour online (see also Araujo et al, 2017;Scharkow, 2016); surveys only produce answers for the questions asked, whereas data measurements can provide more extensive information, especially for activities that change over time. The diary method provides a greater ability to capture change, but only the ones that the users find to be the most important, whereas data measurements capture all activities (Findahl et al, 2014).…”
Section: Example 2: Triangulation Of Big(ger) Data and Virtual Methodmentioning
confidence: 99%